Increases in Brain 1H-MR Glutamine and Glutamate Signals Following Acute Exhaustive Endurance Exercise in the Rat - Świątkiewicz, Maciej; Fiedorowicz, Michał; Orzeł, Jarosław; Wełniak-Kamińska, Marlena; Bogorodzki, Piotr; Langfort, Józef; Grieb, Paweł (Frontiers in Physiology, 2017)
Objective: Proton magnetic resonance spectroscopy (1H-MRS) in ultra-high magnetic field can be used for non-invasive quantitative assessment of brain glutamate (Glu) and glutamine (Gln) in vivo. Glu, the main excitatory neurotransmitter in the central nervous system, is efficiently recycled between synapses and presynaptic terminals through Glu-Gln cycle which involves glutamine synthase confined to astrocytes, and uses 60-80% of energy in the resting human and rat brain. During voluntary or involuntary exercise many brain areas are significantly activated, which certainly intensifies Glu-Gln cycle. However, studies on the effects of exercise on 1H-MRS Glu and/or Gln signals from the brain provided divergent results. The present study on rats was performed to determine changes in 1H-MRS signals from three brain regions engaged in motor activity consequential to forced acute exercise to exhaustion. Method: After habituation to treadmill running, rats were subjected to acute treadmill exercise continued to exhaustion. Each animal participating in the study was subject to two identical imaging sessions performed under light isoflurane anesthesia, prior to and following the exercise bout. In control experiments two imaging sessions separated by the period of rest instead of exercise were performed. 1H-NMR spectra were recorded from the cerebellum, striatum and hippocampus using a 7T small animal MR scanner. Results: Following exhaustive exercise statistically significant increases in the Gln and Glx signals were found in all three locations, whereas increases in the Glu signal were found in the cerebellum and hippocampus. In control experiments no changes in 1H-MRS signals were found. Conclusion: Increase in glutamine signals from the brain areas engaged in motor activity may reflect a disequilibrium caused by increased turnover in the glutamate-glutamine cycle and a delay in the return of glutamine from astrocytes to neurons. Increased turnover of Glu-Gln cycle may be a result of functional activation caused by forced endurance exercise; the increased rate of ammonia detoxification may also contribute. Increases in glutamate in the cerebellum and hippocampus are suggestive of an anaplerotic increase in glutamate synthesis due to exercise-related stimulation of brain glucose uptake. The disequilibrium in the glutamate-glutamine cycle in brain areas activated during exercise may be a significant